Private Activity in Infrastructure Continued Its Recovery in 2006 - World Bank (Washington, DC, 2012)
The report is about the private participation in infrastructure database. Private activity in infrastructure continued its recovery in 2006. The number of projects reaching financial or contractual closure also showed a recovery. The number of private infrastructure projects implemented in 2006 grew by 17 percent to 271 percent. Telecommunications played the biggest part in this: projects reaching closure in 2006 accounted for just 18 percent of the year's investment in the sector, while those closing in previous years represented 82 percent. The recovery in energy investment was driven by six large projects which accounted for 45 percent of commitments in 2006. Finally, new private activity in water focused on smaller projects. The report concludes, continuing the trend of the previous four years, private activity in 2006 was more evenly distributed across regions than it had been during the boom of the late 1990s.